Os efeitos das reclamações online na lealdade dos consumidores: um estudo experimental - Almeida, Tatiane Nunes Viana de (2010)
In an environment of constant change, technological developments, market competition and more informed consumers, the search for a lasting relationship through the conquest of loyalty has become the objective of companies. However, several authors suggest that this loyalty can be affected by negative comments available on the internet. Therefore, this dissertation has as objective to examine if the complaints are available on the internet impact the loyalty to a brand of mobile phone. The research used as the basis the Expanded NCSB model suggest by Johnson et al. (2001), studying five prominent drives of loyalty: image/brand reputation, affective commitment, calculative commitment, perceived value and trust, beyond the satisfaction construct as moderator variable. The research method adopted was the experimental design which included 285 undergraduate students, with the trial which included 285 undergraduate students, with the field study of the mobile industry, specifically, the brands of cell phones. The research approach was quantitative and methods were descriptive statistics, factor analysis, cluster analysis, linear regression and non-parametric test of Wilcoxon for data analysis. Of the 16 hypothesis stemmed from the research model proposed, 12 were confirmed. The results showed that the complaint available on the internet, here represented by the available on the site Reclame Aqui, may impact consumer perceptions about brand loyalty, as well as its antecedents, being that these complaints can affect all the consumers, regardless of historical satisfaction with the brand. It also noted the positive relationship between the independent variables trust, image/brand reputation, perceived value, affective commitment and calculative commitment and the dependent variable - loyalty, even when considering the data obtained after exposure to the complaint. However, no unanimous conclusion that the relationship between these variables was strongest in the group with satisfactory experience. At the first moment of the research, the trust was the most important variable for the formation of loyalty. However, after exposure to treatment, the image/brand reputation, was more relevant. Contributions of the study, limitations and recommendations for future researches are approached in the present investigation